2008
DOI: 10.1007/s12018-008-9021-7
|View full text |Cite
|
Sign up to set email alerts
|

Osteopetrosis: from Animal Models to Human Conditions

Abstract: The term ''osteopetrosis'' is applied to a group of disorders characterized by an increased bone density, due to an inadequate bone resorption. A considerable part of our current knowledge on osteoclast biology is based on the study of osteopetrotic animal models. The search for mutations in these animals has unveiled many molecular mechanisms underlying osteoclast differentiation and functioning. It also supplied new candidate genes for the identification of genes involved in the human variants of this diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 100 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…However, there is no curative therapeutics for ADO2 [ 4 ]. In most patients, they result from heterozygous mutations in CLCN7, which can result in nerve compression syndrome, visual loss and bone marrow failure, and may be presented diverse clinical and radiological manifestations ranging from asymptomatic or relatively mild symptoms to the very severe phenotype [ 2 , 5 ]. Notably, some promising results suggest that small interfering RNA (siRNA)-based therapeutics may be used to cure patients with ADO2 and have been further demonstrated to be feasible in osteoporotic animal models [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no curative therapeutics for ADO2 [ 4 ]. In most patients, they result from heterozygous mutations in CLCN7, which can result in nerve compression syndrome, visual loss and bone marrow failure, and may be presented diverse clinical and radiological manifestations ranging from asymptomatic or relatively mild symptoms to the very severe phenotype [ 2 , 5 ]. Notably, some promising results suggest that small interfering RNA (siRNA)-based therapeutics may be used to cure patients with ADO2 and have been further demonstrated to be feasible in osteoporotic animal models [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent transcriptomic study has been suggested that changes in the expression of ITGB5, PRF1, WARS, and SERPINE2 may be part of the osteoclast phenotype, in addition to the acidification dysfunction caused by heterozygous mutations in the CLCN7 gene in osteoclasts in ADO2 patients [ 13 ]. In the past, knowledge about the molecular characterization and pathogenesis of osteopetrosis was primarily acquired by osteoporotic animal models [ 5 , 16 19 ]. Recently, osteoporotic iPSC models were successfully generated from an ADO2 patient and three autosomal recessive osteopetrosis (ARO) patients, which has provided an unprecedented opportunity for the study of ADO2 pathophysiology and therapeutic application [ 1 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%